2016
DOI: 10.1103/physreve.93.042104
|View full text |Cite
|
Sign up to set email alerts
|

Critical dynamics of the jamming transition in one-dimensional nonequilibrium lattice-gas models

Abstract: We consider several one-dimensional driven lattice-gas models that show a phase transition in the stationary state between a high-density fluid phase in which the typical length of a hole cluster is of order unity and a low-density jammed phase where a hole cluster of macroscopic length forms in front of a particle. Using a hydrodynamic equation for an interface growth model obtained from the driven lattice-gas models of interest here, we find that in the fluid phase, the roughness exponent and the dynamic exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…We study a classical nonequilibrium system in one dimension which shows a jamming transition in the stationary state [28]. The steady state of this model is known exactly [29], and some results for the coarsening dynamics [4,30] and stationary-state dynamics [31] have also been obtained. However, the dynamics of this model under slow annealing have not been studied and here we address this problem using numerical simulations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We study a classical nonequilibrium system in one dimension which shows a jamming transition in the stationary state [28]. The steady state of this model is known exactly [29], and some results for the coarsening dynamics [4,30] and stationary-state dynamics [31] have also been obtained. However, the dynamics of this model under slow annealing have not been studied and here we address this problem using numerical simulations.…”
mentioning
confidence: 99%
“…The stationary-state dynamics have also been studied and it has been found that at the critical point, the steadystate density fluctuations decay on a time scale that grows as L z where the dynamic exponent z = 3/2 [31].…”
mentioning
confidence: 99%
“…The steady state obeys detailed balance and is the same as that in the unidirectional model [28]. As a result, the correlation length exponent ν is given by ( 6); however, the dynamic exponent z = 2 in this case [30].…”
mentioning
confidence: 96%
“…We study a classical nonequilibrium system in one dimension which shows a jamming transition in the stationary state [33]. The steady state of this model is known exactly [28], and some results for the coarsening dynamics [4,29] and stationary state dynamics [30] have also been obtained. However the dynamics of this model under slow annealing have not been studied and here we address this problem using numerical simulations.…”
mentioning
confidence: 99%
See 1 more Smart Citation